Frameworks for ICT policy : government, social and legal issues - Adomi, Esharenana E. (Hershey : Information Science Reference, 2010)
'This book provides policy-relevant insights and information to aid those engaged in systematic research and teaching about ICT policy formation and implementation'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Information technology -- Government policy -- Cross-cultural studies; Information technology -- Security measures -- Cross-cultural studies; Computer crimes -- Prevention -- International cooperation